Effective use of information resource in water supply organisations in Malaysia towards knowledge organisations / Abdul Aziz Abdullah - Abdullah, Abdul Aziz (2002)
Changes in the economic competitions in the world need water supplies authorities to utilise the water supply information source professionally in order to be able fo meet the needs and wants of water supply by demanding sectors. This is so important to upgrade the ability of the organisations towards knowledge organisations. Presently, the opinion of the managers of water supplies organisation incline to the proper and professional information management. However, a survey done on the district managers suggested that the issue of awareness of the importance of proper information management still becoming the stumbling block that resulted less budget a/location and planning given to enhance the information management. As a result not proper attention given towards establishment of effective mechanisms in collaboration among the water supplies organisations to consolidate information under one autonomy. Whilst, indeed the effort should be considered as an urgent matter to improve and maintain the image and the confidence to water supplies industry in Malaysia.